Four-Element MIMO Patch Antenna With High Gain, High Isolation, and Polarization Diversity Characteristics for 28-GHz Applications - Hela Elmannai; Umair Rafique; Hüseyin Şerif Savci; Muhammad Usman Tahir; Mujeeb Abdullah; Abeer D. Algarni; Mariana Dalarsson (International Journal of Antennas and Propagation)
This article presents the design of a high-gain, highly isolated four-element multiple-input multiple-output (MIMO) antenna system operating at the millimeter-wave (mm-wave) 28 GHz frequency band. The radiating element of the MIMO antenna comprises a 1 × 2 array of crescent-shaped patch elements backed by a full ground plane, having overall dimensions of 33 × 33 mm2 (3.08λ × 3.08λ), where λ is the wavelength at 28 GHz. A 0.787-mm-thick low-loss dielectric substrate having a relative permittivity (εr) of 2.2 and a loss tangent (tanδ) of 0.009 is used for the antenna design. It is observed that the designed radiating element provides resonance at 28.18 GHz and has a 6.21% fractional bandwidth (FBW) and a peak realized gain of 10.5 dBi. The radiation and total efficiency of the radiator are noted to be >85% and ≥75%, respectively, in the operating bandwidth. For polarization diversity and high isolation characteristics, the MIMO elements are arranged in an orthogonal manner, which helps achieve an isolation of >22.5 dB for adjacent elements and >32.5 dB for diagonally placed elements in the entire band of interest. Furthermore, MIMO system parameters such as envelope correlation coefficient (ECC) <0.003, diversity gain (DG) >10 dB, total active reflection coefficient (TARC) < −10 dB, and channel capacity loss (CCL) <0.5 bps/Hz are observed, which fall within the operational limits. Based on the achieved outcomes, the proposed design is well suited for mm-wave 28 GHz communication devices.